2020
DOI: 10.1017/s0714980819000527
|View full text |Cite
|
Sign up to set email alerts
|

Nurturing Meaningful Intergenerational Social Engagements to Support Healthy Brain Aging for Anishinaabe Older Adults

Abstract: The emergence of Alzheimer’s disease and related dementias (ADRD) in Indigenous populations across Canada is of rising concern, as prevalence rates continue to exceed those of non-Indigenous populations. The Intergenerativity Model, guided by Indigenous Ways of Knowing, nurtures a psychosocial approach to promoting healthy brain aging and quality of life. Community-based participatory action methods led by interviews, focus groups, and program observations aid in identifying the barriers to and facilitators of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Of these 33 articles, 75% provided a description or definition of the term. These definitions centered on relationship building and integrating scientific, lived experience, and indigenous knowledge to produce new insights ( Cornect-Benoit et al, 2020 ; MacDonald et al, 2006 ). The main values of CBPR identified throughout the literature were attention to equity, collaborative partnerships, bridging knowledge and change, acknowledging expertise beyond academia, attention to culture, and valuing partners’ leadership ( Askari et al, 2018 ; Lee et al, 2018 ; Parker et al, 2022 ).…”
Section: Trends In Terms and Definitions Of Participatory Approaches ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 33 articles, 75% provided a description or definition of the term. These definitions centered on relationship building and integrating scientific, lived experience, and indigenous knowledge to produce new insights ( Cornect-Benoit et al, 2020 ; MacDonald et al, 2006 ). The main values of CBPR identified throughout the literature were attention to equity, collaborative partnerships, bridging knowledge and change, acknowledging expertise beyond academia, attention to culture, and valuing partners’ leadership ( Askari et al, 2018 ; Lee et al, 2018 ; Parker et al, 2022 ).…”
Section: Trends In Terms and Definitions Of Participatory Approaches ...mentioning
confidence: 99%
“…Globally, only 26 studies discussed partnerships with individuals (e.g., residents, caregivers, health-care professionals) from, or organizations serving Indigenous, Black, Asian, or Latinx communities. Some studies reported partnering with Asian practitioners and community members ( Lhimsoonthon et al, 2019 ; Li & Ho, 2019 ; Lindgren et al, 2012 ; Park et al, 2022 ) as well as Indigenous community members ( Acharibasam et al, 2022 ; Cornect-Benoit et al, 2020 ; Cox et al, 2019 ; Dieter et al, 2018 ; Jacklin et al, 2020 ; Pace, 2020 ; Walker et al, 2021 ; Webkamigad et al, 2020 ). In addition, a few studies specified partnering with multiethnic practitioners, caregivers, and community residents ( Goeman et al, 2016 ; Kilstoff & Chenoweth, 1998 ; Nielsen et al, 2022 ).…”
Section: Trends In Partnerships In Adrd Researchmentioning
confidence: 99%
“…Aaniiih Gros Ventres [27], Anishnaabek people of Wiikwemkoong Unceded Territory [43], Arikara-Hidatsa [24], Aztec [44], Caribe [24], Dakota [35], Diné (Navajo) [45], Eastern Cherokee [24], Haida [24], Huichol (Wixarika) [46], Lakota [24], Mayas in the Altos de Chiapas [47], Native Hawaiian [48], Navajo [21], Penobscot [24], Pueblo of Santa Clara [25], Salteaux [42], Seneca [24], Tahltan First Nation [13], Taino [24], Tohono O'odham [24], White Mountain Apache [24], and Yaqui peoples [24] 1 about each Oceania 33…”
Section: Indigenous Groups Articles (N)mentioning
confidence: 99%
“…This means that PCC needs to be modified, if used at all, for Indigenous Elders; this could include reframing PCC as ‘caring for country’ in Australia (McMillan et al, 2010) or ‘going through the full circle of life’ for various First Nations in Canada (Hulko et al, 2010; Jacklin & Walker, 2019; Lanting et al, 2011). Recent research with a variety of First Nations in Ontario has resulted in a culturally sensitive approach to dementia knowledge sharing (Forbes et al, 2013), culturally appropriate information materials (Webkamagid et al, 2020), an intergenerativity model of healthy brain ageing (Cornect‐Benoit et al, 2020) and a culturally safe assessment tool for use with Anishnaabe older adults (Jacklin et al, 2020); however, a culturally safe approach to dementia care has yet to be developed, let alone one that reflects the diversity and specificity of Indigenous nations. Further, the concepts of sensitivity, appropriateness and relevancy are more often appended to culture than is safety.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research with a variety of First Nations in Ontario has resulted in a culturally sensitive approach to dementia knowledge sharing (Forbes et al, 2013), culturally appropriate information materials (Webkamagid et al, 2020), an intergenerativity model of healthy brain ageing (Cornect-Benoit et al, 2020) and a culturally safe assessment tool for use with Anishnaabe older adults (Jacklin et al, 2020); however, a culturally safe approach to dementia care has yet to be developed, let alone one that reflects the diversity and specificity of Indigenous nations. Further, the concepts of 1 A.N.A.C.…”
Section: Introductionmentioning
confidence: 99%